ANALISIS TINJAUAN IMPLEMENTASI METODE AGILE DALAM MANAJEMEN PROYEK SISTEM INFORMASI - Anggita Dwi Inayah (Jurnal Riset Teknik Komputer, 2024)
Information systems project management plays a crucial role in the operations of companies in this digital era, yet it faces numerous challenges due to inherent complexities and dynamics. This literature review aims to explore the effectiveness of the Agile methodology in information systems project management. The research method used is qualitative with a literature review approach, analyzing various studies and scholarly articles related to Agile implementation. The findings indicate that Agile improves responsiveness to change, the quality of the final product, team collaboration and communication, and risk management. Agile allows for quick adjustments to changing needs and priorities through short iterative cycles and strengthens teamwork through regular meetings and continuous feedback. In conclusion, adopting the Agile methodology provides significant benefits and is highly recommended as a strategy to enhance the efficiency and effectiveness of information systems project management in a dynamic business environment.